Payback clauses in Europe : supporting company investment in training ; final report - (:unkn) unknown (Publications Office of the European Union, 2012)
"Payback clauses are a legal instrument that may encourage companies to invest in training by allowing them to bind employees for a certain period of time after training in return for providing the training. In fact, employees are free to move to another company but may be requested to reimburse the cost of the training, or part of the cost.This Cedefop report provides an overview of whether payback clauses for employer-financed training are regulated in 33 European countries, and if so how they are regulated. In-depth analysis is carried out for eight selected countries: Germany, Italy, Luxembourg, the Netherlands, Romania, Slovakia, Sweden and the UK. The report is largely based on information collected in surveys of key national stakeholders - representatives of ministries, employers’ organisations and trade unions - and from company cases. The analysis of legal framework covers aspects such as: the level of regulation (national law, collective/sectoral level agreements and individual/company level agreements) and the conditions laid down in law (contractual retention period, types of training and categories of employees/contracts that payback clauses may apply to, costs to be reimbursed by employees, redemption form, etc.). The results of research show that there is relatively little information on the practical use of payback clauses: their implementation (the extent to which the payback clauses are actually included in employment contracts and training agreements) and enforceability (when reimbursement of training costs was indeed requested by employer).On the basis of information collected, the strengths and weaknesses of the instrument are discussed. Finally, recommendations for policy, research and practice are formulated." (Hrsg. , BIBB-Doku)
Keywords: S 1.5.3 Betriebliche Weiterbildung; S 4.1 Finanzierungsquellen; S 2.1.6 Arbeits- & Tarifrecht; I 2.2 Europa; Betriebliche Weiterbildung; Weiterbildungsfinanzierung; Weiterbildungsrecht; Arbeitsrecht; Europa